Arabidopsis BIRD Zinc Finger Proteins Jointly Stabilize Tissue Boundaries by Confining the Cell Fate Regulator SHORT-ROOT and Contributing to Fate Specification. Issue 4 (31st March 2015) - Long, Yuchen; Smet, Wouter; Cruz-Ramírez, Alfredo; Castelijns, Bas; de Jonge, Wim; Mähönen, Ari Pekka; Bouchet, Benjamin P.; Perez, Gabino Sanchez; Akhmanova, Anna; Scheres, Ben; Blilou, Ikram
Abstract : Tissue boundary establishment and cell fate specification require BIRD proteins to regulate SHORT-ROOT signaling and transcriptional activities, highlighting the developmental plasticity in plants. Abstract: Plant cells cannot rearrange their positions; therefore, sharp tissue boundaries must be accurately programmed. Movement of the cell fate regulator SHORT-ROOT from the stele to the ground tissue has been associated with transferring positional information across tissue boundaries. The zinc finger BIRD protein JACKDAW has been shown to constrain SHORT-ROOT movement to a single layer, and other BIRD family proteins were postulated to counteract JACKDAW's role in restricting SHORT-ROOT action range. Here, we report that regulation of SHORT-ROOT movement requires additional BIRD proteins whose action is critical for the establishment and maintenance of the boundary between stele and ground tissue. We show that BIRD proteins act in concert and not in opposition. The exploitation of asymmetric redundancies allows the separation of two BIRD functions: constraining SHORT-ROOT spread through nuclear retention and transcriptional regulation of key downstream SHORT-ROOT targets, including SCARECROW and CYCLIND6 . Our data indicate that BIRD proteins promote formative divisions and tissue specification in the Arabidopsis thaliana root meristem ground tissue by tethering and regulating transcriptional competence of SHORT-ROOT complexes. As a result, a tissue boundary is not "locked in" after initial patterning like in many animal systems, but possesses considerable developmental plasticity due to continuous reliance on mobile transcription factors.